Group V secretory PLA(2) regulates TLR2-dependent eicosanoid generation in mouse mast cells through amplification of ERK and cPLA(2)α activation - Kikawada, Eriya (American Society of Hematology, 2007)
Mast cells may be activated through Toll-like receptors (TLRs) for the dose- and time-dependent release of eicosanoids. However, the signaling mechanisms of TLR-dependent rapid eicosanoid generation are not known. We previously reported a role for group V secretory phospholipase A(2) (PLA(2)) in regulating phagocytosis of zymosan and the ensuing eicosanoid generation in mouse resident peritoneal macrophages, suggesting a role for the enzyme in innate immunity. In the present study, we have used gene knockout mice to define an essential role for MyD88 and cytosolic PLA(2)α in TLR2-dependent eicosanoid generation. Furthermore, in mast cells lacking group V secretory PLA(2), the time course of phosphorylation of ERK1/2 and of cPLA(2)α was markedly truncated, leading to attenuation of eicosanoid generation in response to stimulation through TLR2, but not through c-kit or FcεRI. These findings provide the first dissection of the mechanisms of TLR-dependent rapid eicosanoid generation, which is MyD88-dependent, requires cPLA(2)α, and is amplified by group V sPLA(2) through its regulation of the sequential phosphorylation and activation of ERK1/2 and cPLA(2)α. The findings support the suggestion that group V sPLA(2) regulates innate immune responses.